Hypoglycemic Activity and Safety Assessment of Pediococcus acidilactici Strain DNH16 in Experimental Type 2 Diabetes Mellitus Rats Induced with Streptozotocin - Edy Fachrial; Juliana Lina; Harmileni Harmileni; Sari Anggraini; Widya Yanti Sihotang (Indonesian Biomedical Journal, 2024)
BACKGROUND: Type 2 diabetes mellitus (T2DM) cases tend to rise throughout the year in all parts of the world. The α-glucosidase inhibitors are frequently used to both prevent and treat T2DM. This α-glucosidase inhibitor activity is seen in some probiotic species, and a certain strain of Pediococcus acidilactici exhibits promising characteristics as an α-glucosidase inhibitor. This study was conducted to assess the hypoglycemic activity and safety of P. acidilactici strain DNH16 (PADNH16) in experimental rats with T2DM induced by streptozotocin.